Actualization Of The Forms Of Patriotism In Indonesia - Kamrussamad, Muhamad Ali Embi (International Journal of Advanced Science and Technology, 2020)
In the era of globalization, the spirit of patriotism has become increasingly important to be explored andpracticed. This is because the Indonesian state is inhabited by people who are different in terms ofreligion, ethnicity and ideology. If every Indonesian met, understood ethnicity, political ideology, or ahigher and foremost party from the Indonesian state itself, then surely the Indonesian state would not beable to achieve development and improvement. In this diverse Indonesian society, important patriotismamong its people is important. Through high patriotism, it will only be able to deter individuals inIndonesian society before choosing prejudists and radicals against any religion, ethnicity, ideology oreven those who do not join them.This prevailing phenomenon has raised the question of whether people really consider the purpose ofpatriotism? or is patriotism understood in a narrow form? That is, the community is only required to fightto take up arms in the compilation state against the enemy when in a safe environment the communitydoes not need to care about the state of the country. It may also be that the public is mistaken with theconcept of patriotism with the agreement that patriotism only applies in symbolic form, whereas thecommunity agrees to state symbols such as leaders, flags or national anthem associations which arecommunicated by the state that have been successfully declared.The important question that addresses the spirit of patriotism is very interesting to study. Especially inIndonesian society which consists of various layers of society. Through this study we will be able todiscuss patriotism as well as the forms of patriotism that Indonesian society has today based ondemographics.